RGD-HSA-TAC nanoparticles targeted delivery of tacrolimus and attenuation of podocyte injury in diabetic kidney disease - Zhaochen Guo; Shaohui Gao; Feng Xu; Zige Chen; Qinger Wang; Zhaojie Liu; Ziyue Wang; Weisong Qin; Caihong Zeng; Zhihong Liu; Hao Bao (Journal of Nanobiotechnology)
Abstract Background Diabetic kidney disease (DKD) is a prevalent and severe complication of diabetes and plays a pivotal role in the pathogenesis and progression of DKD. However, the current clinical application of the treatment methods does not yield effective results. Tacrolimus has been utilized in the management of immune-mediated and genetic-mediated nephropathy, with an emphasis on the restoration of podocyte cytoskeletal integrity and inhibition of apoptosis. The clinical management of diabetic nephropathy with tacrolimus remains challenging because of the risk of worsening hyperglycemia and infection. Results We developed two RGD-HSA-TAC nanoparticles designed for targeted delivery of tacrolimus to podocytes. Administration of SANPs and CNPs resulted in elevated levels of tacrolimus in podocytes, leading to a reduction in podocyte damage and albuminuria in diabetic nephropathy mice. Furthermore, the use of SANPs and CNPs resulted in a decrease in tacrolimus accumulation in the pancreas, lymph nodes, and thymus, thereby reducing the potential to exacerbate hyperglycemia and infection. Importantly, compared to tacrolimus alone, both SANPs and CNPs demonstrated superior therapeutic efficacy, with CNPs exhibiting a greater advantage over SANPs. Conclusions Compared to tacrolimus, SANPs and CNPs demonstrated superior therapeutic efficacy and a reduced incidence of adverse effects in the treatment of diabetic nephropathy. Graphical abstract